Knowledge and attitude of nursing students regarding pediatric palliative care in a teaching nursing institute - Dinabndhu Barad; Kalpana Panda; Soumya Satpathy; Neelanjana Jena; Nirupama Behera; Syed Ghulam Mustafa; Jayeeta Dey; Jami Bikrant Kumar Prusty (Journal of Education and Health Promotion)
Background: According to the World Health Organization, palliative care (PC) for children involves actively caring for the child’s health, mind, and spirit and supporting the family. Pediatric palliative care (PPC) is characterized as a comprehensive strategy for both the child with a fatal illness and his or her family during their tragedy. The study aims to assess nursing students’ knowledge and attitudes regarding PPC and determine the association with selected sociodemographic variables. Materials and Methods: This descriptive (cross-sectional observational) study was carried out by SUM Nursing College, Bhubaneswar from November 2022 to October 2023 by using three tools (a self-structured questionnaire on sociodemographic data, a standardized questionnaire on knowledge, and a standardized questionnaire on attitude) to assess the level of knowledge and attitude among study participants toward PPC. Nursing students who have already been exposed to pediatric subjects such as B.Sc. 3rd and 4th year, GNM 2nd and 3rd year, and all nursing students of post basic B.Sc, and M.Sc., were included in the study. Result: Based on the investigation, it was discovered that among 223 of the total study sample, 39.5% had good knowledge, and the remaining 60.5% had poor knowledge. In addition, when the attitude of nursing students was analyzed, it was found that 54.3% of the total study sample had positive attitudes, and the remaining 45.7% had negative attitudes toward PPC. Conclusion: As nurses play a major role in delivering PPC, it could be included as a mandatory part in their educational curriculum. A similar study can be replicated among other healthcare professionals in several areas regarding PPC.